.Oil Cities in Africa: Beyond Just Transition. (23rd June 2021) - Obeng‐Odoom, Franklin
Abstract: Nations and NGOs are promoting the idea of a transition from a petroleum‐based civilization to one fueled by renewable energy. But there are many questions about how to proceed. The solution usually proposed is to develop "clean energy" as the underlying basis of a transition. Analysts tend to be concerned with climate change and land use change, with a focus on technical developments. Socio‐ecological issues receive scant attention, especially if they relate to oil cities. This article starts from the perspective that progress in saving the planet from destruction can only be achieved by taking seriously past and present injustices and taking measures to rectify them. I use the situation in Port Harcourt, Nigeria to illustrate this proposition. I focus on three interrelated concepts: rent theft, social costs, and just transition. The central problem is rent theft because it is at the root of the "crime of poverty" and the social costs of plundering the land for energy sources. Until they address problems arising from historical injustice, campaigns for a just transition that promote clean energy in a bioeconomy will merely reproduce the central problem. Thus, reparations and land equity must be an integral part of any solution.